1995
DOI: 10.1177/088626095010004006
|View full text |Cite
|
Sign up to set email alerts
|

Jealousy and Romantic Attachment in Maritally Violent and Nonviolent Men

Abstract: This study investigated whether maritally violent males are more jealous than maritally nonviolent males. The subjects were 180 cohabiting men divided into four groups selected on dimensions of marital violence, marital satisfaction, and amount of counseling. Multivariate analyses of covariance (MANCOVAs) revealed significantly elevated jealousy levels in the two abusive groups and also in the unsatisfactorily married, nonviolent group. Indeed, jealousy correlated negatively with marital satisfaction level. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
7

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 36 publications
4
38
0
7
Order By: Relevance
“…Previous research has consistently found jealousy to be significantly related to IPV Barnett et al, 1995;Dutton, van Ginkel, & Landolt, 1996;Fenton & Rathus, 2010;Puente & Cohen, 2003;Sugarman & Hotaling, 1989;Wilson & Daly, 1998). The predictive strength of jealousy was supported in this research, even when differentiation of self was added to the analysis.…”
Section: Summary and Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Previous research has consistently found jealousy to be significantly related to IPV Barnett et al, 1995;Dutton, van Ginkel, & Landolt, 1996;Fenton & Rathus, 2010;Puente & Cohen, 2003;Sugarman & Hotaling, 1989;Wilson & Daly, 1998). The predictive strength of jealousy was supported in this research, even when differentiation of self was added to the analysis.…”
Section: Summary and Discussionsupporting
confidence: 72%
“…Most of the studies on IPV have examined risk factors for physical IPV such as relational satisfaction and marital conflict (Cano & Vivian, 2003;Lawrence & Bradbury, 2001;Panuzio & DiLillo, 2010;Schumacher & Leonard, 2005;Stith et al, 2008;Stith at al., 2004b), romantic jealousy (Babcock, Costa, & Green, 2004;Barnett, Martinez, & Bluestein, 1995;Hannawa, Spitzberg, Wiering, & Teranishi, 2006;Wilson & Daly, 1998;, and depression and anxiety (Boyle & Vivian, 1996;Maiuro et al, 1988;Pan et al, 1994;Vivian & Malone 1997). However, little research existed on the relationship of differentiation of self and physical IPV.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, a negative relationship exists between satisfaction and overall jealousy experience (e.g., Barnett, Martinez, & Bluestein, 1995;Buunk, 1981) and for both cognitive and emotional jealousy (Anderson et al, 1995;Guerrero & Eloy, 1992). However, exceptions to the negative relation between jealousy and satisfaction also exist.…”
Section: Relational Satisfactionmentioning
confidence: 99%
“…The distinction between the two polarities is relatively clear only when one is faced with an apparent psychosis [6]. Morbid jealousy is a relevant phenomenon related to negative emotions, and to a range of destructive events, harassment, or behavior, such as domestic violence and marital problems [13,14]. There is also evidence that it is one of the most relevant motivations in passionate murders [15,16], and 57% of former-intimate stalking victims have reported that their partner had been jealous during the relationship [17].…”
Section: Introductionmentioning
confidence: 99%